The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.21500/20112084.2320
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Symmetry by Comparing the Acquisition of Symmetric and Nonsymmetric Conditional Relations in a Capuchin Monkey

Abstract: Article history: Received: 15-04-2016 Revised: 29-06-2016 Accepted: 12-08-2016 Key words: conditional discrimination; equivalence class formation; symmetry; Sapajus sppThe present study presents a procedure to assess the property of symmetry by comparing the acquisition of conditional relations that are consistent and inconsistent with this property in a capuchin monkey (Sapajus spp.). One young male monkey underwent arbitrary matching-to-sample training. The experiment had four phases: Phase 1.1 (establishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In Campos et al (2011), four pigeons showed evidence for symmetry in a simultaneous successive discrimination procedure, but follow‐up tests (Campos et al, 2015) showed that those results could be explained by primary stimulus generalization for all but one pigeon. Finally, the better performance on symmetry relative to nonsymmetry trials in Soares Filho et al (2016) could be a result of stimulus discriminability, which was not tested in that study. These studies underscore the need to conduct stimulus control analyses on observed emergent performances to confirm a true positive finding.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In Campos et al (2011), four pigeons showed evidence for symmetry in a simultaneous successive discrimination procedure, but follow‐up tests (Campos et al, 2015) showed that those results could be explained by primary stimulus generalization for all but one pigeon. Finally, the better performance on symmetry relative to nonsymmetry trials in Soares Filho et al (2016) could be a result of stimulus discriminability, which was not tested in that study. These studies underscore the need to conduct stimulus control analyses on observed emergent performances to confirm a true positive finding.…”
Section: Discussionmentioning
confidence: 74%
“…Soares Filho et al (2016) conducted a systematic replication of Velasco et al (2010) in one capuchin monkey. There were four training phases: AB training followed by BA testing in which relations consistent with symmetry were reinforced and CD training followed by DC testing in which relations inconsistent with symmetry were reinforced.…”
Section: Developments Since 2007mentioning
confidence: 99%
“…It turns out that three studies using only A-B training, and the alternative testing approach of transfer effects, did find weak evidence for symmetry in pigeons (Hogan & Zentall, 1977) or capuchin monkeys (D'Amato et al, 1985;Soares Filho et al, 2016). The strategy used to reveal bidirectionality was to train participants with two or more A-B pairings, and subsequently have them learn reversed pairings that were either consistent (B1-A1, B2-A2, etc.…”
Section: Transfer Effects In Conditional Matching-to-sample (Cmts) St...mentioning
confidence: 99%
“…Moreover, stimulus preference may have accounted for the results. Last, Soares-Filho et al (2016) trained one capuchin monkey on two pairings tested with consistent reversals, then on two new pairings tested with inconsistent reversals. A difference in learning length for reversed pairings suggested symmetry; however, no control was provided for the possibility that inconsistent pairings were intrinsically harder to learn than consistent ones (e.g., due to stimulus choice), nor for an effect of condition order (e.g., the second test may take longer simply due to boredom).…”
Section: Transfer Effects In Conditional Matching-to-sample (Cmts) St...mentioning
confidence: 99%
“…The idea that multiple exemplar training with symmetry relations might be necessary for animals to show emergent symmetry may seem a plausible account for the human–animal differences, as human children are naturally exposed to such training in infancy. However, a number of studies have failed to show consistent emergent symmetry even after providing multiple exemplar training in a variety of nonhuman species including chimpanzees (Dugdale & Lowe, 2000; Yamamoto & Asano, 1995), capuchin monkeys (Brino et al, 2014), pigeons (Gomez et al, 2014; Lionello‐DeNolf & Urcuioli, 2002; Navarro & Wasserman, 2020; Soares Filho et al, 2016; Velasco et al, 2010), and rats (Bruce et al, 2022).…”
mentioning
confidence: 99%